Chronic manganese poisoning and striatal adenylate cyclase activity - Bonilla, Ernesto (Investigación Clínica, 2013)
Striatal adenylate cyclase activity was markedly decreased in rats ingesting 2.5, 5 and 10 mg Mn/ml of water during 8 months. No stimulation of the enzymatic activity by dopamine was observed in any of the animals whatever the concentration of manganese ingested in the drinking water.